Influence of the addition of organic residues on carbohydrate content and structural stability of some highland soils in Ethiopia - Spaccini, R.; Piccolo, A.; Mbagwu, J.S.C.; Zena Teshale, A.; Igwe, C.A. (Soil use and management, 2002)
. When over exploited and coupled with climatic conditions, tropical soils are subject to increased erosion and a loss of soil organic matter. Countermeasures include the incorporation of organic materials such as crop and animal residues. We studied the effect of adding crop residues and manure to soil, at five sites in Ethiopia, on carbohydrate properties, aggregate stability and the C and N distribution within water‐stable aggregates. The effects of organic amendments varied between sites. The largest content of carbohydrates was obtained in the control treatment at Holeta, Ginchi (90 kg ha–1 mustard meal), Jimma (5 t ha–1 cow dung + 9 t ha–1 coffee husk), Awassa (forested soil), and Sirinka (soil alley‐cropped with Leuceanae). The aggregate stability of these soils was highly correlated with the OM content but not with carbohydrates. The smaller aggregates (<1.00 mm) accumulated more carbohydrates than the larger (>1.00 mm), thereby suggesting a protecting effect within the finer soil fractions. A protecting role played by humified OM components was also indicated by the C and N distribution as well as the C:N ratios which showed preferential accumulation in small rather than in large aggregates. The isotopic 13C‐OC values of carbohydrate extracts were generally low, suggesting that OM was from plants with C3 photosynthetic pathways. Soil treatments with maize alone or combined with coffee husks at Jimma decreased the δ13C‰ values slightly, revealing that maize contributed a share of the labile OM. Despite the improvement in the soil OM content, neither the carbohydrate content nor the aggregate stability were increased to the level of the forested sites, suggesting that the additions of crop residues and manure were not alone sufficient to restore the soil physical quality.